2019
DOI: 10.1002/ece3.4930
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic emissions of Sorex unguiculatus (Mammalia: Soricidae): Assessing the echo‐based orientation hypothesis

Abstract: Shrew species have been proposed to utilize an echo‐based orientation system to obtain additional acoustic information while surveying their environments. This system has been supported by changes in vocal emission rates when shrews encounter different habitats of varying complexity, although detailed acoustic features in this system have not been reported. In this study, behavioral experiments were conducted using the long‐clawed shrew ( Sorex unguiculatus ) to assess this orientation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Moreover, shrews have developed an additional possibility to explore the immediate environment, namely echolocation ( Forsman and Malmquist 1988 ; Siemers et al. 2009 ; Sanchez et al. 2019 ), making them less dependent on vision.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, shrews have developed an additional possibility to explore the immediate environment, namely echolocation ( Forsman and Malmquist 1988 ; Siemers et al. 2009 ; Sanchez et al. 2019 ), making them less dependent on vision.…”
Section: Resultsmentioning
confidence: 99%
“…Under all three conditions, the shrews emitted a variety of calls, including clicks and several tonal pulse types ranging in frequency between 5 and 45 kHz with durations of 3-40 ms. While several studies have shown that shrews and tenrecs do show context-dependent changes in vocalization rate, there is little direct evidence for echolocation by these animals (Buchler 1976;Tomasi 1979;Forsman and Malmquist 1988;Siemers et al 2009;Sanchez et al 2019).…”
Section: Orientation and Echolocationmentioning
confidence: 98%
“…Streaked tenrecs (Hemicentetes semispinosus) emitted clicks of low intensity; while those of Nesogale dobsoni were audible to humans at 7 m. Gould et al (1964) found that, contrary to the audible pulses of tenrecs, shrews (Sorex vagrans, S. cinereus, S. palustris, and Blarina brevicauda) searching for the platform emitted ultrasonic pulses with most energy between 30 and 60 kHz. The pulses were about 5 ms in duration with inter-pulse intervals of about 20 ms. Sanchez et al (2019) recorded five Sorex unguiculatus in three different experimental setups, including soft and hard barrier obstacles. Under all three conditions, the shrews emitted a variety of calls, including clicks and several tonal pulse types ranging in frequency between 5 and 45 kHz with durations of 3-40 ms.…”
Section: Orientation and Echolocationmentioning
confidence: 99%
“…The vocalizations of shrews are still insufficiently known. Loud sounds of high frequency are known from a number of genera and species (Konstantinov & Movčan 1985), such as Crocidura (Hutterer & Vogel 1977, Hutterer & López-Jurado 1990, Simeonovska-Nikolova 2004, Diplomesodon (Movčan & Šibkov 1982, Konstantinov & Movčan 1985, Neomys (Hutterer 1978, Köhler & Wallschläger 1987, Shibkov et al 2001, Köhler 2012, Sorex (Hutterer 1976, 1982, Movčan & Šibkov 1982, Köhler 1998, Sanchez et al 2019, and Suncus (Hutterer et al 1979, Schneiderová 2014. Some species even echolocate (Gould et al 1964, Buchler 1976, Forsman & Malmquist 1988 or use echo orientation (Siemers et al 2009).…”
Section: Introductionmentioning
confidence: 99%